Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian UMKM Kuliner Kecamatan Baros, Kabupaten Serang - Banten - Febri Hayati; Siti Optapiani; Alma Herlina; Riki Gana Suyatna (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze the influence of brand image and product quality on the purchasing decisions of culinary SMEs in the Baros District, Serang, Banten. The focus is to provide in-depth insights into key factors that can enhance the attractiveness and sustainability of culinary SMEs at the local level. The research method employed is a quantitative approach, with the population encompassing all consumers in the Baros District who have shopped at culinary SMEs. The sample consists of 60 respondents, selected using non-probability purposive sampling. Data were collected through questionnaires and analyzed using t-tests and F-tests with the assistance of SPSS software version 29.0. Based on the partial test results, both brand image (regression coefficient 0.790, t-value 9.310) and product quality (regression coefficient 0.794, t-value 9.592) significantly influence purchasing decisions (both p < 0.05). Regression analysis indicates that simultaneously, brand image and product quality also have a significant impact on purchasing decisions (F-value 51.517 > F-table 3.16, p < 0.05).